Intravoxel incoherent motion MRI for discrimination of synovial proliferation in the hand arthritis: A prospective proof‐of‐concept study. Issue 4 (31st January 2019) - Fujimori, Motoshi; Murakami, Koichi; Sugimori, Hiroyuki; Lu, Yutong; Sutherland, Kenneth; Oki, Nozomi; Aoki, Takatoshi; Kamishima, Tamotsu
Abstract : Background: Postcontrast‐enhanced MRI is currently the reference standard for synovial proliferation in rheumatoid arthritis (RA). However, the technique is somewhat invasive due to the use of gadolinium contrast agents, which may cause severe adverse/side effects. Intravoxel incoherent motion (IVIM) simultaneously permits quantification of perfusion as well as diffusion using a single imaging scan. Purpose/Hypothesis: To test the capability of IVIM MRI for noninvasive discrimination of synovial proliferation in hand arthritis. Study Type: Prospective. Subjects: Seven suspected RA patients (three women and four men; mean age, 61 years; range, 26–74 years). Field Strength/Sequence: 3 T/short tau inversion recovery (STIR), IVIM, postcontrast‐enhanced MRI. Assessment: Region of interest (ROI) was identified based on STIR. Contrast‐enhanced MRI was evaluated using a 5‐point grading scale of 0 (water) to 4 (synovial proliferation) according to the degree of contrast enhancement within the ROI. For each ROI, we calculated the apparent diffusion coefficient (ADC) and IVIM parameters (molecular diffusion coefficient [D], perfusion fraction [ f ], and perfusion‐related diffusion coefficient [D*]). These parameters were subsequently compared with ROI contrast enhancement grades. Statistical Tests: Spearman's rank correlation test and a receiver operating characteristic (ROC) curve. Results: A total of 90 ROIs of suspected synovial proliferation and/or joint effusion were identified. ROI grades were correlated with ADC and D values ( r S = –0.385, P < 0.001, r S = –0.458, P < 0.0001, respectively), but not with the f and D* values ( r S = –0.010, P = 0.936, r S = –0.084, P = 0.505, respectively). The area under the curves (AUCs) of D values (0.708–0.888, P = 0.002–0.0002) were slightly larger than those of ADC values (0.692–0.791, P = 0.013–0.001) when comparing low‐ vs. high‐contrast enhancement grades. Data Conclusion: The IVIM parameter D and ADC may be useful for the noninvasive identification of synovial proliferation in hand arthritis. Level of Evidence : 2 Technical Efficacy Stage : 2 J. Magn. Reson. Imaging 2019;50:1199–1206.